Glossary of healthcare pathways: a methodological approach involving a transdisciplinary team in public health - Laurie Fraticelli; Elise Verot; Elise Verot; Elise Verot; Hans-Martin Späth; Marine C. Genton; Cédric Kempf; Celine Clement; Celine Clement; Adeline Darlington-Bernard; Sylvain Roy; Claude Dussart; et al. (Frontiers Media S.A., 2024)
IntroductionThe healthcare pathway is at the heart of public health organization concerns, but communication between the various players can be an obstacle. This work, produced by a French transdisciplinary team, offers a methodological approach based on formalized consensus to elaborate a glossary of healthcare pathways. A two-steps procedure was elaborated, including a double rounded Delphi method to formalize expert consensus, and two groups of experts: a workgroup and a review group.MethodsThe workgroup provided a list of words or expressions that, in their opinion, described, evaluated or compared the healthcare pathways for patients, caregivers or regulators. The review group checked this list and added or deleted words or expressions. Then, definitions were added by the workgroup based into account three dimensions: official, academic and from the field. The review group validated the definitions and provided complementary proposals if needed.ResultsAfter pooling the list of words proposed by each of the six members of the working group, 417 words/expressions were ranked. After the two rounds of evaluation, 294 words/expressions were rated "appropriate" and were analyzed by the review group. This group, after two rounds of evaluation, agreed on 263 words/expressions that were transmitted to the working group who defined them. These definitions were rated by the review group. The first round of evaluation established 195 definitions as being appropriated whereas 68 definitions were amended by the review group.ConclusionThis glossary supports transdisciplinary communication, reduces the extent of variations in practice and optimizes decision-making. International debate on all aspects might be strengthened by an improved understanding of the concept of health pathway.